2018
DOI: 10.1002/ijc.31252
|View full text |Cite|
|
Sign up to set email alerts
|

The efficacy and safety of anti‐PD‐1/PD‐L1 antibodies combined with chemotherapy or CTLA4 antibody as a first‐line treatment for advanced lung cancer

Abstract: Checkpoint inhibitors show promising efficacy in advanced lung cancer, especially in non-small-cell lung cancer (NSCLC). This meta-analysis was conducted to explore the therapeutic efficacy and safety of anti-PD-1/PD-L1 antibodies combined with chemotherapy or CTLA4 antibody as first-line treatments for patients with advanced lung cancer. A systematic search was performed in databases for this system review and quantitative meta-analysis. Twelve trials were finally enrolled in the meta-analysis. Our analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…The third question is whether additional ICIs to the first‐line chemotherapy is necessary for patients with low or negative expression for PD‐L1. Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first‐line treatment of advanced NSCLC . With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD‐L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The third question is whether additional ICIs to the first‐line chemotherapy is necessary for patients with low or negative expression for PD‐L1. Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first‐line treatment of advanced NSCLC . With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD‐L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first-line treatment of advanced NSCLC. 28,29 With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD-L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs. When stratified by PD-L1 expression, patients with negative PD-L1 expression can further benefit from combination therapy in mOS, mPFS, and ORR, regardless of atezolizumab or pembrolizumab.…”
Section: Discussionmentioning
confidence: 59%
“…The combined ORRs of I, C and I + C were 32, 32 and 50%, which illustrated that the population to receive benefit from PD‐1/L1 and chemotherapy might be different, while a combined strategy would not only prolong patients’ life expectancy but also benefit more people. Xu et al conducted a meta‐analysis based on the majority of phase I and II clinical trials, they observed significant improvement in PFS but not in OS of checkpoint inhibitors (PD‐1/L1 or CTLA‐4) with chemotherapy as a first‐line treatment compared to chemotherapy. We included the latest phase III international RCTs and also did the indirect comparison, with the purpose of reporting the efficacy and safety of PD‐1/L1 Inhibitors, chemotherapy and their combination in front‐line treatment of NSCLC according to PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported synergistic treatment of anti-PD-1 and anti-CTLA-4 had high response rate and durable response with tolerable safety profile. 44,45 These exploratory investigations showed encouraging clinical activity and feasibility of combination therapies. New combinations of ICIs with classical chemotherapy and/or radiotherapy will further revolutionize the treatment of NSCLC.…”
Section: E1457600-4mentioning
confidence: 98%